2022
DOI: 10.1371/journal.pone.0269915
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome analysis of genus Forsythia related constituents in Forsythia suspensa leaves and fruits using UPLC-ESI-QQQ-MS/MS technique

Abstract: Forsythia suspensa is a traditional Chinese herb. Its numerous metabolites have important roles, as they possessed a wide range of biological activities. This study explored the accumulations of F. suspensa metabolites by performing widely targeted metabolomic analysis. The metabolites were studied at four stages of fruit development. Metabolites in the fruits and leaves of F. suspensa during fruit development included phenolic acids, flavonoids, lipids, lignans and coumarins, amino acids and their derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Demethylation modification enhances its molecular reactivity (Huan et al, 2021). PHI-Der had been prepared by removing the methyl group of the ortho-methoxy group from the phenolic hydroxyl group, but this method only removed one methyl group (Liu et al, 2022). In a previous study, the ideal molecular weight of PHI-Der was 330.33; however, mass spectrometry showed a characteristic peak at 313.32, which may be because of the unstable connection of the hydroxyl group (Hannah et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Demethylation modification enhances its molecular reactivity (Huan et al, 2021). PHI-Der had been prepared by removing the methyl group of the ortho-methoxy group from the phenolic hydroxyl group, but this method only removed one methyl group (Liu et al, 2022). In a previous study, the ideal molecular weight of PHI-Der was 330.33; however, mass spectrometry showed a characteristic peak at 313.32, which may be because of the unstable connection of the hydroxyl group (Hannah et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study showed that the water extract of F. suspensa (WFS) has beneficial effects against aberrant osteoclast differentiation and estrogen deficiency‐induced bone loss (Hwang et al, 2019). The phytochemical profile of WFS indicated that abundant alkaloids, lignans, phenylethanoids, terpenes, flavonoids, and steroids components might attribute to anti‐osteoporotic activity (Liu et al, 2022). Among these constituents, Phillygenin (Phi) is one of the components that have not been reported in bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography‐mass spectrometry (LC‐MS) exhibits high separation capacity and sensitivity, 16 and LC‐MS‐based plant metabolomics has been widely used in the chemical analysis of herbal medicines, such as Ginseng, 17 Forsythia suspensa , 18 Salvia Miltiorrhiza , 19 and Astragali Radix 20 . In our research, an ultra‐high‐performance liquid chromatography to quadrupole time‐of‐flight mass spectrometry (UHPLC‐Q‐TOF‐MS) was used to characterize the chemical compounds in BR first, and then, the impact of intercropping on the chemical constituents of B. chinense was investigated by metabolomics coupled with various chemometric methods.…”
Section: Introductionmentioning
confidence: 99%